Zora Neale Hurston: Scientist, Folklorist, Storyteller - Mary Catherine Russell (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2017)
This paper examines the life and work of Zora Neale Hurston and her contribution to American literature in the 20th Century. While previous critical analysis of Hurston’s work has focused primarily on her most popular novel, Their Eyes Were Watching God, this paper examines Hurston’s career by taking a holistic approach to the body of her literary works. Hurston’s early career as an anthropologist is shown to provide a foundation for her later interest in folklore. In turn, her connection and participation in the Harlem Renaissance gave Hurston’s writing a nuanced and individualized style as part of the American modernist movement. Examining the tri-partite nature of Hurston’s identity leads to the most comprehensive and accurate understanding of the works Hurston produced in her lucrative career as a scientist, folklorist, and author.
Keywords: Zora Neale Hurston; Anthropology; Harlem Renaissance; Modernism; Folklore; Ethnography